Aeschnosoma yelenae sp. nov. from French Guiana (Odonata: Corduliidae), with notes on its phylogenetic affinities and bionomics - Fleck, Günther; Mézière, Nicolas (Zootaxa, 2024)
Aeschnosoma yelenae sp. nov., based on a single male specimen, is described from lowland coastal forest (Sinnamary) in French Guiana. This species belongs to the auripennis-group and seems to be closely related to Aeschnosoma heliophila Fleck known from a single watershed in a Brazilian elevated plateau in western Bahia State (part of Cerrado) impacted heavily by agro-industrial activities. The shape of the anal appendages, especially the distal fifth of the cerci being bent at a right angle in dorsal view, is the most convenient structural character to separate this species from its congeners. Like A. heliophila, the new species flies in sunshine several metres above the ground in clearings dotted with shrubs surrounded or bordered by a dense formation of taller trees.